Using the Multiple Correspondence Analyses to Study the Addiction of Drug and Alcohol in Iraq - Abdul Razzak Rasheed, Aseel; A. Rasheed, Husam; J. Sadik, Nazik (International Journal of Psychosocial Rehabilitation, 2020)
Drug and alcohol addiction are a social problem that emerged last decade in Iraq. In this study, we discuss the problem of an addiction by using multiple correspondence analyses (MCA). MCA is one of the multivariate methods, as it is used to study the correlation strength that exists between more than two categorical variables. The data is classified according to Iraqi governorates, gender, and patient status (inpatient or outpatient). A relation between variables was clarified through the Burt matrix. Our results show that drug addiction is larger than alcohol addiction in all Iraqi governorates. The main reason for drug addiction is taking it continuously without consulting a specialist.